Analisis Kesulitan Menulis Puisi Bebas Siswa Kelas V SDN Sanggarahan - Prabowo, Mahendra Putra; Cahyaningtyas, Andarini Permata (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research was designed using qualitative research method with case study type. The purpose of this study is to find out what are the difficulties of students in writing free poetry and to find out the influence of language skills and vocabulary on the quality of poetry written by grade V students of SDN Sanggrahan. The subjects of this study were 13 fifth grade students. Data collection used observation, interview, and documentation techniques. Data analysis techniques include data reduction, data presentation, and conclusion drawing. This research was conducted in January - February 2025. This study shows the results that there are still difficulties in writing free poetry. This can be seen in the results of students' free poetry, most students write free poetry without using diction, imagery, inappropriate language style, rhyme, and rhythm. As a result, the results of students' poetry writing do not show the overall physical and inner structure of free poetry. As well as the lack of vocabulary mastery and language skills make poetry writing less than optimal.